Urgent issues and prospects in guilty plea research and practice - Redlich, Allison D. (Legal and criminological psychology, 2025)
Criminal legal systems around the world rely heavily on defendants foregoing their right to trial and pleading guilty. However, legal scholars, social scientists, and practitioners have identified and empirically examined numerous problems with pleas, such as the high potential for coercion, innocent defendants falsely pleading guilty, and undue incentives in exchange for accepting plea offer. In this article, leading guilty plea experts (practitioners and researchers) were asked to identify what they considered to be the most urgent questions surrounding pleas. Across nine commentaries, three primary themes emerged. First were calls for increased transparency in pleas, specific to rules of discovery and access to exculpatory information, and in uncovering the hidden nature of the plea negotiation process. Second were concepts of fairness and voluntariness, such as uncounseled pleas, particularly for misdemeanour defendants, and the dubious assumptions made by courts regarding the presumption of voluntariness. Third was the theme of fair and just outcomes, particularly false guilty pleas. Four of the commentaries focused on innocence, describing and encouraging more research on the factors that increase false guilty pleas, including excessive plea discounts, specialized sentencing offers for juvenile defendants, and ‘time-served’ offers, either to induce initial guilty pleas (pre-trial phase) or to avoid official exonerations of those wrongly convicted (post-conviction phase). Across all commentaries, experts identified areas in need of future research, both in continuing to understand the problems known to plague systems of pleas and in developing improved methods to ensure the guilty plea process is transparent, voluntary, and just.